Amelia Earhart : young aviator - Gormley, Beatrice; Henderson, Meryl (New York Aladdin Paperbacks, 2000)
A biography of the pilot who was the first woman to fly alone across the Atlantic and who was later lost at sea, attempting to fly around the world.
Z
950
Z
Keywords: Earhart, Amelia, -- 1897-1937 -- Juvenile literature; Earhart, Amelia, -- 1897-1937 -- Childhood and youth -- Juvenile literature; Earhart, Amelia, -- 1897-1937.; Women air pilots -- United States -- Biography -- Juvenile literature; Air pilots; Women -- Biography